2022
DOI: 10.3390/nu14051012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dietary Quality Based on Intelligent Ordering System and Chinese Healthy Eating Index in College Students from a Medical School in Shanghai, China

Abstract: We intended to precisely evaluate the dietary quality of male and female medical college students using canteen data from the “Intelligent Ordering System” (IOS), combined with the supplemental food frequency questionnaire (SFFQ) and the Chinese Healthy Eating Index (CHEI) in Shanghai, China, to explore the potential factors influencing dietary quality. A total of 283 college students with the average age of 24.67 ± 3.21 years and Body Mass Index of 21.46 ± 3.49 kg/m2 in the medical school were enrolled in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…Despite attaching high importance to healthy eating, <10% of the current students met the recommendations of ≥5 servings/day, slightly lower than among young adults in the general German population [ 61 ]. We also observed sex differences in healthy nutrition (52% female vs. 32% male consumed ≥ 3 servings of vegetables/fruits per day), concurring with Finland, Nigeria, and China [ 17 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Despite attaching high importance to healthy eating, <10% of the current students met the recommendations of ≥5 servings/day, slightly lower than among young adults in the general German population [ 61 ]. We also observed sex differences in healthy nutrition (52% female vs. 32% male consumed ≥ 3 servings of vegetables/fruits per day), concurring with Finland, Nigeria, and China [ 17 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 80%
“…Likewise, our MSc and PhD students differed significantly in meeting the SB recommendations, supporting that SB significantly increased from freshmen to senior students [ 16 ]. As for nutritional habits, we found only that significantly more MSc than BSc students considered healthy eating important, and more PhDs met both the FVC and water intake recommendations, concurring with the USA and China, where graduate students rated healthy eating significantly higher, and more frequently achieved the FVC recommendations than undergraduates [ 19 , 120 ]. Academic level was also associated with sleep quality, where more of our BSc than MSc/PhD students had impaired sleep, congruent with Ethiopia [ 32 ], and partially supporting Taiwan, where freshmen had shorter sleep duration than seniors, but seniors had higher sleep latencies [ 36 ].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…For example, it can be extended to participants in other countries, as long as they are also higher education students, given they particularities differentiating from other target groups, like general young adults. Many studies confirmed the singularities of the higher education students in what concerns food literacy and eating behaviors in different countries: Bangladesh [ 67 ], Belgium [ 68 ], China [ 69 ], Croatia [ 70 ], Egypt [ 70 ], Greece [ 70 ], Hungary [ 71 ], Italy [ 70 ], Jordan [ 72 ], Korea [ 73 ], Poland [ 74 ], Portugal [ 70 , 75 ], Serbia, [ 76 ], Slovenia [ 70 ], Spain [ 56 , 77 ], Syria [ 78 ], and the United States [ 79 ].…”
Section: Discussionmentioning
confidence: 99%